Factors affecting the acceptability of COVID-19 vaccine in the postpartum period - Deniz Oluklu; Sule Goncu Ayhan; Dilek Menekse Beser; Derya Uyan Hendem; Eda Ozden Tokalioglu; Ezgi Turgut; Dilek Sahin (Taylor & Francis Group, 2021)
Background Coronavirus disease 2019 (COVID-19) has spread rapidly around the world, causing massive morbidity and mortality. Vaccination during puerperium protects both the mother and the newborn and is important to keep the pandemic under control. Methods Women who gave birth at Ankara City Hospital between February 11, 2021 and March 21, 2021 were included. Data were collected through a face-to-face questionnaire. Results We asked 412 postpartum women were surveyed about their acceptance of the COVID-19 vaccine; 137 (33.3%) of them wanted to be vaccinated, while 275 (66.7%) of them did not want to be vaccinated. Reasons for vaccination rejection; 209 (76%) of them stated that there was not enough information about the safety of the vaccine for the postpartum period, and 89 (32.4%) of them thought that the vaccine would not be effective for the disease. Three of the answers in the survey were found significantly different in high-risk pregnancy (HRP) group compared to low-risk pregnancy (LRP) group; 1) Having their babies to be vaccinated, 2) To be vaccinated if it will be recommended to the puerperal women, and 3) Feeling anxious about being infected by SARS-CoV-2 (p < .05). Conclusions Health authorities recommend the COVID-19 vaccine to breastfeeding mothers. However, a relatively low vaccination acceptance rate was observed in the present study. For newly developed vaccines, concern over vaccine safety is the biggest obstacle to vaccine administration. Therefore, the reasons that influence acceptance or refusal of vaccines are important for developing targeted communication strategies and healthcare policies.